2005
DOI: 10.2460/ajvr.2005.66.1544
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary arterial disease in cats seropositive for Dirofilaria immitis but lacking adult heartworms in the heart and lungs

Abstract: Cats with serologic evidence of exposure to heartworms, including those without adult heartworms in the lungs and heart, have a greater prevalence of pulmonary arterial lesions than heartworm-negative cats without serologic evidence of exposure. Additional studies are needed to define the pathogenesis, specificity, and clinical importance of these lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0
1

Year Published

2011
2011
2025
2025

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 15 publications
4
29
0
1
Order By: Relevance
“…The result is diminished pulmonary function, hypoxemia, dyspnea, and cough; in some cats, this can lead to chronic respiratory disease. These findings provide evidence that pulmonary disease occurs in heartworminfected cats, even when the infection does not progress to the adult worm stage, by inducing a strong vascular and parenchymal inflammatory response (53,69,114). This pronounced bronchoreactivity has been hypothesized to be due to the activity of pulmonary intravascular macrophages, a component of the reticuloendothelial system that cats, but not normal dogs, possess (118).…”
Section: Clinical Features Of Human and Animal Dirofilariasis Heartwomentioning
confidence: 81%
“…The result is diminished pulmonary function, hypoxemia, dyspnea, and cough; in some cats, this can lead to chronic respiratory disease. These findings provide evidence that pulmonary disease occurs in heartworminfected cats, even when the infection does not progress to the adult worm stage, by inducing a strong vascular and parenchymal inflammatory response (53,69,114). This pronounced bronchoreactivity has been hypothesized to be due to the activity of pulmonary intravascular macrophages, a component of the reticuloendothelial system that cats, but not normal dogs, possess (118).…”
Section: Clinical Features Of Human and Animal Dirofilariasis Heartwomentioning
confidence: 81%
“…Research has demonstrated that the early immature adult infection is associated with an intense inflammatory response Dillon, 2008;Holmes et al, 1992;Selcer et al, 2005). In addition, clinical experience and a prospective clinical study of cats with suspected heartworm disease has indicated that some cats will get the early infection, the worm(s) will die, but the cat will continue to develop chronic inflammatory lung disease , and lung pathology continue to be present after the infection (Browne et al, 2005).…”
Section: Introductionmentioning
confidence: 94%
“…Sections were scored on a scale of 0-3 individually for interstitium, bronchus, bronchioles, pulmonary arterioles, and major pulmonary artery areas (Browne et al, 2005;Dillon et al, 2013). The right caudal lung at the mid-lobar cross-section, corresponding to a plane and location of CT slice, was used for section for evaluation.…”
Section: Histopathologymentioning
confidence: 99%
“…In assays of each of these cats, in contrast to cats harboring adult heartworms, antibody concentration declined at subsequent time points and became negative or weak positive by day 270 p.i. Identification of cats that harbor immature worms with no evidence of adult worms is important because (Browne et al 2005).…”
Section: Discussionmentioning
confidence: 99%